Massacres of tamils 1956-2008
This book painstakingly records massacres that occurred between 1956 – 2008 from first hand information. Although the book is by no means complete the compilers have done a commendable job recording part of contemporary history without leaving it to future historians. Our gratitude is due to all individuals and institutions who laboured hard under trying conditions to compile this book. These massacres were carried out by the Sinhala armed forces ably aided and abetted by racist Sinhala politicians. The genocidal war against the Thamil people has killed more than 100,000 Thamils since 1956. In the last phase of the Eelam War IV (May, 2009) 25,000 civilians died and twice that number were seriously injured. Sadly some among them are some of those who worked on this project.